Polylingual Environment in the South of Bessarabia: Problems of Speech Culture - Melnikova, Ruslana; Anhelovska, Kateryna; Vakar, Alexandra (Journal of Danubian Studies and Research, 2023)
The article discusses the main aspects and ways of forming a culture of students’ speech in general secondary education institutions in Southern Bessarabia. It is noted that the formation of communicative competence takes place in three directions: enrichment of vocabulary, assimilation of literary language norms, development of coherent speech, etc.